Is differential diagnosis attainable in disarticulated pathological bone remains? - Assis, Sandra (2018)
IF/00127/2014/POSDOC IF/00127/2014/CP1233/CT0003 SFRH/BPD/82559/2011 IF/00127/2014 UID/ANT/04038/2013